Factors affecting gross-flow microfiltration of dispersions - Mikulášek, Petr (Univerzita Pardubice, 1999)
This paper deals with the use of microfiltration in fouling dispersion and discusses the means available to the process designer to minimize the effects of fouling and take them into account when performing the design. The results of recent work which show how the characteristic parameters of membrane (pure water flux and pore size distribution), the effects of operating parameters (composition of dispersion, cross-flow velocity, transmembrane pressure), and the feed flow management (hydrodynamic) methods to improving the flux (the crossflow system in the presence of a fluidized bed and the rotating membrane system) can contribute to the minimisation of fouling and process optimalization.
Keywords: mikrofiltrace; disperzní systémy; membrány; Optimalizace